Understanding the role of the family physician in early psychosis intervention - Kelly K. Anderson; Suzanne Archie; Richard G. Booth; Chiachen Cheng; Daniel Lizotte; Arlene G. MacDougall; Ross M. G. Norman; Bridget L. Ryan; Amanda L. Terry; Rebecca Rodrigues (BJPsych Open, 2018)
BackgroundThe family physician is key to facilitating access to psychiatric treatment for young people with first-episode psychosis, and this involvement can reduce aversive events in pathways to care. Those who seek help from primary care tend to have longer intervals to psychiatric care, and some people receive ongoing psychiatric treatment from the family physician.AimsOur objective is to understand the role of the family physician in help-seeking, recognition and ongoing management of first-episode psychosis.MethodWe will use a mixed-methods approach, incorporating health administrative data, electronic medical records (EMRs) and qualitative methodologies to study the role of the family physician at three points on the pathway to care. First, help-seeking: we will use health administrative data to examine access to a family physician and patterns of primary care use preceding the first diagnosis of psychosis; second, recognition: we will identify first-onset cases of psychosis in health administrative data, and look back at linked EMRs from primary care to define a risk profile for undetected cases; and third, management: we will examine service provision to identified patients through EMR data, including patterns of contacts, prescriptions and referrals to specialised care. We will then conduct qualitative interviews and focus groups with key stakeholders to better understand the trends observed in the quantitative data.DiscussionThese findings will provide an in-depth description of first-episode psychosis in primary care, informing strategies to build linkages between family physicians and psychiatric services to improve transitions of care during the crucial early stages of psychosis.Declaration of interestNone.